Obesity and adolescent lifestyles : a 6-year longitudinal study in Portuguese boys and girls - Leitão, Raquel (2010)
There has been increasing research on the relationships between adolescent lifestyle and obesity in Portuguese youth. However, most studies have been cross-sectional. We aimed to investigate food habits, physical activity, sedentary behaviour and psychosocial characteristics in adolescents with different adiposity development trajectories. Anthropometric measurements were obtained in 288 children, firstly at age 9 and later at age 15. Lifestyle and psychosocial characteristics were assessed at age 15 by questionnaires. Percentage of body fat (%BF) derived from skinfolds was calculated. Obesity was defined by the cut-offs of 25%BF in boys and 30%BF in girls. Based on adiposity status at each assessment, four adiposity trajectories were identified: “never obese”, “remained obese”, “return to normal”, and “became obese”. Logistic regression modelling was used to examine associations between adolescent lifestyles characteristics and changes in obesity status. Gender differences were much less evident among adolescents who remained obese than in those who were never obese. The most consistent associations in the multivariate models were found for easiness/difficulty of finding new friends and for time spent with physical activity. Adolescents who reported finding it difficult to make new friends were more likely to become obese than those reporting it easy (OR=5.67; p=0.03), taking the group “never obese” as reference. Those who spent more time being physically active were less likely to become obese (OR=0.09; p=0.02) and were more likely to reverse obesity (OR=6.73; p=0.02) in comparison to the group “remained obese”. The results suggest that obese status attenuates adolescent lifestyle gender-related differences and reinforce the relevance of physical activity for both the prevention and treatment of obesity. Integrated strategies focusing on physical activity may be the key to effectively fight against obesity and also to foster adolescents’ psychosocial well-being.